Influence of Dentin Priming with Tannin-Rich Plant Extracts on the Longevity of Bonded Composite Restorations - Polassi, Mackeler Ramos; Oliveira, Thales de Sá; de Carvalho, Ana Calheiros; Medeiros, Lívia Soman de Medeiros; Veiga, Thiago André Moura; Graeff, Carlos Frederico de Oliveira [UNESP]; González, Alejandra Hortencia Miranda [UNESP]; Marcucci, Maria Cristina [UNESP]; Grecco, Simone Dos Santos; D'Alpino, Paulo Henrique Perlatti [UNESP] (Hindawi, 2021)
Objective: This in vitro study evaluated the influence of bioactive plant extracts as dentin biomodifying agents to improve the longevity of bonded restorations. For that, plant extracts were applied to the dentin surface prior to the adhesive system. Materials and Methods: Bovine incisors were ground flat to obtain 2 mm thick slices in which conical preparations were made (N = 10). Tannin-containing plant extracts were applied to dentin before the application of the restorative system, as follows: control group (untreated, CTL), chlorhexidine 0.12% (CHX), mastruz (Dysphania ambrosioides, MTZ), cat's claw (Uncaria tomentosa, CTC), guarana (Paullinia cupana, GUA), galla chinensis (Rhus chinensis, GCH), and tannic acid (extracted from Acacia decurrens, TNA). The push-out bond strength test was conducted (0.5 mm/min). Dentin biomodification was assessed by the modulus of elasticity and mass change in bovine tooth sections (0.5 × 1.7 × 7.0 mm). The dentin staining after extract treatments of dentin slices was compared. The dentin surface wettability was also evaluated by means of the contact angles of the adhesive system with the dentin surface and compared with the untreated control group. Data were subjected to ANOVA/Tukey's test (α = 0.05). Results: The bond strength of the restoratives to dentin was not significantly improved by the plant extracts, irrespective of the evaluation time (p > 0.05). Except for TNA, the elastic modulus of demineralized dentin significantly reduced after treatment with the plant extracts (p < 0.05). The dentin staining correlated with the tannin content of the extracts. The contact angle was significantly reduced when treated with CTC, GCH, and TNA. Conclusions: The tannin-containing extracts had a questionable effect on the longevity of bonded restorations. The dentin modulus was negatively affected by the extract treatments. Although some of the extracts changed the contact angle, which seems to improve the adhesive monomer permeation, the tannin-rich plant extract application prior to adhesive application was proven to be clinically unfeasible due to dentin staining.